Impact of copper and zinc mixture on bacterial flora of digestive tract of rainbow trout (oncorhynchus mykiss) - Syvokiene, Janina; Vosyliene, Milda Zita (Journal of Environmental Engineering and Landscape Management, 2013)
The effects of 96-hour exposure and within 12 days after exposure to 0.25, 0.125, 0.06 portions of the 96-hour LC50 of CuZn ions mixture on microbiological parameters of rainbow trout digestive tract were studied evaluating quantitative and functional characteristics of bacteria. The extinction of proteolytic bacteria was found in fish affected by 0.25 portion of the 96-hour LC50 of metal mixture. The recovery of proteolytic bacteria was determined in fish exposed to 0.125 and 0.06 portions of the 96-hour LC50 of CuZn ions mixture after 8 days of keeping fish in clean water. The abundance of the investigated functional groups of bacteria was gradually recovering to the control level after 12 days of keeping fish in clean water.First published online: 11 Feb 2013